MENGEMBANGKAN KEMAMPUAN GURU MENYUSUN SOAL HIGHER ORDER THINKING SKILLS MELALUI BIMBINGAN TEKNIS DI SMP NEGERI 1 SINDUE TAMBUSABORA - Mahfud Mahfud; Suyuti Suyuti; Idrus Idrus; Windayanti Windayanti; Wilman Wilman; Nuraedah Nuraedah (Jurnal Abdimas Bina Bangsa, 2022)
This community service activity is entitled "Developing Teachers' Ability to Compile Higher Order Thinking Skills Through Guidance and Training at SMP Negeri 1 Sindue Tambusabora." This service was carried out because of the main problem of partner schools, namely that they have not been able to compile HOTS questions. This problem is also associated with; 1) not conducting a basic competency review before developing a grid of questions; 2) did not compile a grid of HOTS questions; 3) not formulating indicators about HOTS; 4) do not make a HOTS question card; 5) not assembling standardized questions (HOTS); and 5) not to follow up in the form of a qualitative review of the HOTS question items. To overcome partner problems, it is carried out with a Technical Guidance (Bimtek) solution. This bimtek is packaged in 4 (four) stages, namely; 1) Preparation; 2) preparation of Bimtek materials; 3) Implementation of Bimtek; and 4) evaluation and follow-up. The results of this service are: 1) teachers at partner schools understand well and correctly the concept of compiling a grid of HOTS questions; 2) teachers at partner schools understand well and correctly the concept of compiling indicators of HOTS questions according to the ABCD formula; and 3) teachers at partner schools understand well and correctly the concept of drafting HOST. The outputs of this devotion are: 1) the lattice of HOTS questions according to the subject family; and 2 HOTS questions according to the subject family